In situ Investigations of Interfacial Degradation and Ion Migration at CH3NH3PbI3 Perovskite/Ag Interfaces - Xiong Li; Hong-he Ding; Gui-hang Li; Yan Wang; Zhi-min Fang; Shang-feng Yang; Huan-xin Ju; Jun-fa Zhu (化学物理学报（英文版）, 2019)
Interfacial properties between perovskite layers and metal electrodes play a crucial role in the device performance and the long-term stability of perovskite solar cells.Here,we report a comprehensive study of the interfacial degradation and ion migration at the interface between CH3NH3PbI3 perovskite layer and Ag electrode.Using in situ photoemission spectroscopy measurements,we found that the Ag electrode could induce the degradation of perovskite layers,leading to the formation of PbI2 and AgI species and the reduction of Pb2+ ions to metallic Pb species at the interface.The unconventional enhancement of the intensities of I 3d spectra provides direct experimental evidences for the migration of iodide ions from CH3NH3PbI3 subsurface to Ag electrode.Moreover,the contact of Ag electrode and perovskite layers induces an interfacial dipole of 0.3 eV at CH3NH3PbI3/Ag interfaces,which may further facilitate iodide ion diffusion,resulting in the decomposition of perovskite layers and the corrosion of Ag electrode.